Hydrocyclone investigation and modelling at medium feed solids concentration of mixed minerals - M. A. Doheim; M. N. M. Ahmed; S. A. Sayed (The Institute of Materials, Minerals and Mining, 1995)
The performance of a 12.7 cm hydrocyclone was investigated by considering the effect of design variables (diameters of the vortex finder and apex) and operating variables (pressure drop and solids content of the feed) at a medium feed solids concentration of mixed minerals. Cut-size was found to be the most important parameter in hydrocyclone design and operation. The effect of feed pressure in reducing hydrocyclone cut-size is less pronounced at medium feed solids concentration with a mixed mineral feed. The choice of vortex finder diameter and apex diameter becomes more sensitive at medium feed solids concentrations. The effect of feed solids concentration in increasing the cut-size becomes less marked at higher concentrations. Predictions of an empirical model were found to be in good agreement with experimental data. Comparison of results obtained from the model with those predicted by theoretically derived models showed the latter to be more promising, with the turbulent two-phase model giving closer agreement with the experimental data